THE UNCERTAINTIES OF WORK IN THE CANE FIELDS IN PONTAL OF PARAPANEMA REGION - SP - Barreto, Maria Joseli [UNESP]; Thomaz Junior, Antonio [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
The text reflects on the uncertainties of work in the cane fields in Pontal of Parapanema region, before the closure and bankruptcy of the sugarcane agro-industries installed in the west of Sao Paulo State. In 2010, for example, the region had ten agribusiness installed and operating in the processing of sugarcane; However, in subsequent years four units were disabled. In this context, thousands of workers lost their jobs, and do not receive labor rights (salary, 13th salary, vacation, FGTS, INSS - Social Security, etc.), and yet the workers were exposed to a series of humiliations due to labor agreements not met by the contracting companies.
Keywords: Work; unemployment; sugarcane agribusiness; Pontal of Parapanema